Qur’anic Studies in the Global Academic Sphere: Bibliometric Mapping of Research Themes, Collaborations, and Emerging Directions - Jamil, Ahmad; Khaled, Nashwan Abdo (Tribakti: Jurnal Pemikiran Keislaman, 2025)
The study of Qur’anic Sciences has long been a central focus within Islamic scholarship, yet comprehensive mapping of its global trajectories, collaborations, and emerging themes remains insufficiently addressed. This study aims to critically analyze the dynamics of Qur’anic Studies in the global academic sphere by identifying dominant themes, evaluating patterns of scholarly collaboration, and exploring the extent to which the field is diversifying into new disciplinary domains. Bibliometric analysis was employed as the primary method, using bibliographic data indexed in Scopus between 2001 and 2025. Harzing’s Publish or Perish (PoP) facilitated quantitative analysis, while VOSviewer was utilized for visualizing co-authorship networks, institutional clusters, and thematic density. The findings reveal that Qur’anic Studies continues to be shaped by individualistic scholarship, with a low co-authorship rate averaging one author per publication and moderate citation performance, reflected in an h-index of 7 and a g-index of 9. Thematic mapping highlights the persistent dominance of research on tafsir, hermeneutics, and contextual approaches, but also shows emerging directions connecting the Qur’an with education, public health, digital technology, and interfaith dialogue. Geographically, Southeast Asia—particularly Indonesia and Malaysia—emerges as the most productive hub, while Middle Eastern and Western institutions remain influential yet less collaborative across regions. Theoretically, this study underscores a critical paradox: while the field is experiencing thematic diversification, its fragmented networks and limited methodological innovations risk confining Qur’anic Studies to regional silos rather than advancing it as a globally dialogical discipline. Strengthening transnational collaboration, fostering interdisciplinary approaches, and promoting embodied engagement with contemporary issues are necessary steps to reposition Qur’anic Studies as a central node in broader academic and intellectual discourses.